"Why don't you think of Malaysia?" - Narratives on Educational Migration, Emotions, and Social Capital among Transnational Students. Issue 1 (26th November 2015) - Carlson, Marie; Jacobsson, Bengt
Abstract: This contribution is about a female transnational student from Turkey, Hafize, studying for four years at an Islamic Malaysian university. She was interviewed during the research project "Transnational Student Mobility in Higher Education in Asia", a multi-sited ethnographic project containing six sub-studies aiming to illuminate student voices and the impact of cultural processes on student-inhabited transnational spaces, identity negotiations, and networks. Through a bottom-up perspective, and with life story as the principal method, the project illustrates processes of social change and relations between the individual and society. Questions are posed about, inter alia, the motivations and reasons that may be identified in the educational stories. Hafize's narrative is discussed as a relational and contextual story, in which family relations and the significance of education, gender, ethnicity, religion, and socio-economic and political situations intersect. Education is given different meanings: instrumental and reflexive as well as emotional aspects. Turning points and the concept of capital, especially social and emotional capital, are addressed. Hafize's family of eight siblings is deeply involved in serial reciprocity, a tightly bonded network supporting all the children in their efforts to study. Hafize's story is substantially gendered and 'ethnified' – a reflexive emotional identity project, in which education and religion are given high priority. In Turkey secularist legislation was an obstacle. The studies abroad provided possibilities for self-development but tempered with some limitations.